Formulasi Effervescent Rumput Laut sebagai Antihipertensi - Mandiricha, Tara; Inassani, Lustyafa; Malik, Ibnu; Harum, Zahrotul Hasanah; Setiawan, Meddy (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Eucheuma spinosum belongs to rhodophyceae seaweed that comprises bioactive peptides. Those peptides worked by decreasing blood pressure, i.e. ACE inhibitor drugs. These studies are conducted to determine reaction of Eucheuma spinosum distribution as natural ACE inhibitor in form of effervescent formulation. These study were true experimental wiith pre-post test only control group. Sample consists of 28 Wistar rats, divided into 4 groups; a group of control (K) and 3 groups of experiment (P1, P2, P3) were given Eucheuma spinosum, dose 200 mg/kgBW/day, 400 mg/kgBW/day, & 600 mg/kgBW/day. The result shows that there is an effect of Eucheuma spinosum distribution to the blood pressure of hypertensive rats.Keywords : Effervescent Eucheuma spinosum, hypertension, bioactive peptide, ACE Inhibitor